PROBLEMATIC ISSUES OF ІNFORMATION DISCLOSURE IN THE PROCESS OF FORMING THE FINANCIAL REPORTING SYSTEM, ESTABLISHED ON THE BASIS OF IFRS TAXONOMY - MYKYTYUK, NATALIYA; DUNAIEVSKA, ANASTASIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
For consolidation with the global business space, Ukraine encourages both businesses and government institutions to introduce innovative changes in the practice of accounting and in the formation and presentation results of activities in the form of financial statements. The information provided in the reporting should be reliable, transparent, timely and useful for financial market participants, including in terms of financial statements analysis, risk assessment and business attractiveness. Qualitative disclosure of information, according to international standards, contributes to the integration of the domestic economy into the international economic community, improving the efficiency of the investment climate. In order to quickly exchange information data and access to business information of stakeholders, Ukraine should contribute the process of implementing a single Financial Reporting System, based on Taxonomy, according to international standards (IFRS) in a single electronic format based on the iXBRL standard. Due to the fact that the number of companies reporting under IFRS is increasing every year, the issue of information disclosure is relevant, taking into account the peculiarities of financial reporting in Ukraine. The article outlines the institutional conditions for the need to introduce a reporting system on the bases Taxonomy according to international standards. The advantages of such a process are outlined for both of those reliable for compiling such reports and for different types of its users. . The technical features of the financial statements formation in iXBRL format are considered, in particular regarding the use of software and validation of information entered. Some problematic issues are described, which are due to the inconsistency of the some IFRS translations with the need to reflect the materiality of information in the financial statements.